SCHEME OF ETHYLENE TELOMERIZATION REACTION (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
During the telomerization reaction of ethylene with methyl alcohol, isopropyl alcohol is formed using a system consisting of hydrogen peroxide and acetone as a catalyst. Ethylene acts as a monomer, and methyl alcohol serves as a telogen. The process begins with the formation of telomers corresponding to the initial alcohol. The reaction follows a free radical mechanism, starting with the interaction of hydrogen peroxide with acetone.